The Psychoeducation Effect on the Emotional Mental Disorders Symptoms of Covid-19 Pandemic Survivors - Arfianto, Muhammad Ari; Ibad, Muhammad Rosyidul; Widowati, Sri; Aryani, Hening Ryan (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2022)
The Covid-19 pandemic has had an impact on mental and emotional disorders in society. It made psychosomatic symptoms and maladaptive behavior for health. Psychoeducation could be a solution to improve healthy behavior so that it could prevent the occurrence of more severe mental disorders. This study aimed to determine the psychoeducation effect on the emotional mental disorders symptoms in communities affected by the COVID-19 pandemic. This study used a quasi-experimental method of pretest posttest control group design. The sample was 76 respondents who lived in East Java. The respondents were divided into 2 groups. 38 respondents in the first group received psychoeducation about mental health and psychosocial support through online media. Variables were measured using the Self Report questionnaire 20 and analyzed by the Wilcoxon sign rank test and the Mann-Whitney test. The intervention had a significant effect on decreasing the respondents' symptoms of mental emotional disorders with p value < 0.001. The study also found that there was a significant difference between the treatment group and the control group with p value